ANALYSIS OF THE NEEDS FOR DIGITAL-BASED DIGITAL-BASED TEACHING MODULES INTEGRATED HIGH LEVEL THINKING SKILLS - Mardhatillah Mardhatillah; Zaki Al Fuad; Helminsyah Helminsyah; Musdiani Musdiani (Sensei International Journal of Education and Linguistic, 2022)
This study aims to analyze the development needs of the development of digitally integrated KBAT-based thematic elementary school teaching modules. The research was conducted using a survey method at 9 (nine) elementary schools in Aceh Besar and Banda Aceh districts. The research subjects were 18 classroom teachers who taught thematic learning. The objects studied were the responses of school principals and teachers to the development of KBAT integrated digital-based elementary thematic teaching module development, the tendency of teachers to apply thematic models in school learning, student reasoning, and student character. Data were collected by interviews, questionnaires, observations, and tests. Data were analyzed descriptively. The results of the analysis show that (1) school principals have not provided guidance on developing thematic models, so they support development efforts.